2004
DOI: 10.1590/s0037-86822004000500004
|View full text |Cite
|
Sign up to set email alerts
|

Co-infecção HIV e vírus da hepatite B: prevalência e fatores de risco

Abstract: The objective of this study was to assess the prevalence of hepatitis B virus and possible risk factors for this disease in 401 patients infected with the human immunodeficiency virus, followed at the University Hospital of the Ribeirão Preto Medical School, São Paulo State University. Each participant was submitted to a specific questionnaire and had a blood sample tested for the serologic markers HBsAg, total anti-HBcAg, anti-HBsAg and anti-HCV, using ELISA technique. The overall prevalence of hepatitis B ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 20 publications
2
4
2
5
Order By: Relevance
“…e seroprevalence rate in this study is comparable with rates of 8.2-8.3% reported among apparently healthy pregnant women in Nnewi, Yola, and Zaria [17][18][19]. Similar seroprevalence rates were also reported in ailand (8.7%) [20], Brazil (8.5%) [21], Dar es Salaam (8.8%) [22], and India (8.35%) [23]. HBV prevalence in this study is higher than 4.1% reported among apparently healthy adolescents in Abakaliki, Southeastern Nigeria [8], 4.7% among HIV patients in Port-Harcourt, Southern Nigeria [24], and 6.02% among children enrolled in an antiretroviral treatment programme in Uyo, South-southern Nigeria [25].…”
Section: Discussionsupporting
confidence: 87%
“…e seroprevalence rate in this study is comparable with rates of 8.2-8.3% reported among apparently healthy pregnant women in Nnewi, Yola, and Zaria [17][18][19]. Similar seroprevalence rates were also reported in ailand (8.7%) [20], Brazil (8.5%) [21], Dar es Salaam (8.8%) [22], and India (8.35%) [23]. HBV prevalence in this study is higher than 4.1% reported among apparently healthy adolescents in Abakaliki, Southeastern Nigeria [8], 4.7% among HIV patients in Port-Harcourt, Southern Nigeria [24], and 6.02% among children enrolled in an antiretroviral treatment programme in Uyo, South-southern Nigeria [25].…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of HBV infection among HIV-infected patients measured in this study (26.2%) was lower than those reported in sub-Saharan Africa (59.8%), 16 Chile (46.3%), 17 Cuba (45.5%) 18 and in different regions of Brazil, which ranges from 30.0% to 55.1%. 4,5,7,19,20 The prevalence of HIV-HBV coinfection (2.5%) in the present study was lower than those reported in different regions of Brazil (5.7%, 8.5%, and 18%). 4,5,21 In addition, our results were in line with the prevalence of HIV-HBV coinfection from the state of Mato Grosso, also located in Central-West Region of Brazil.…”
Section: Discussioncontrasting
confidence: 74%
“…4,5,7,19,20 The prevalence of HIV-HBV coinfection (2.5%) in the present study was lower than those reported in different regions of Brazil (5.7%, 8.5%, and 18%). 4,5,21 In addition, our results were in line with the prevalence of HIV-HBV coinfection from the state of Mato Grosso, also located in Central-West Region of Brazil. 20 In the population-based multicentric survey of hepatitis B infection conducted in urban area of Central-West Region of Brazil, the region was classified as a low HBV endemic area based on the encountered prevalence.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Embora em proporção inferior, o HCV também pode ser transmitido por exposição percutânea a sangue ou plasma contaminados, sendo o risco de aquisição por acidente perfurocortante estimado entre 3% e 10% (GERBERDING, 1994;GERBERDING, 2003;HENDERSON, 2003;KIYOSAWA;SODEYAMA;TANAKA, 1991;LANPHEAR et al, 1994;PURO et al, 1995;STELLINI et al, 1993). Há vários relatos na literatura de aquisição do HCV após injúrias com material perfurocortante (KIYOSAWA;SODEYAMA;TANAKA, 1991;SEEFF, 1991;VAGLIA et al, 1990) e a transmissão desse agente associado ao HIV, após perfuração com agulha, também foi descrita (ARAÚJO et al, 2000;RIDZON et al, 1997).…”
Section: Segundo a Organização Mundial Da Saúde A Concepção De Saúdeunclassified